RULES FOR CARCOREPULMONARY RESUSCITATION - Xaydarova Dilafruz (New modern researchers: modern proposals and solutions, 2025)
Cardiopulmonary resuscitation (CPR), cardiopulmonary resuscitation is a set of emergency measures aimed at restoring the vital functions of the body and removing it from a state of clinical death. CPR includes 100-120 compressions of the chest to a depth of 5-6 cm per minute. The resuscitator can also perform artificial ventilation of the lungs (artificial respiration); for non-specialists, a simplified method is recommended, which includes only chest compressions. The compression to breath ratio for adults should be 30 to 2.